Mediastinal migration of distal occipito-thoracic instrumentation - Joseph, Vivek (Springer-Verlag, 2007)
We present the occurrence and management of mediastinal migration of the distal aspect of a posterior occipito-thoracic screw–rod construct. No similar occurrence was found in the literature. This event occurred following an emergency tracheotomy (requiring neck hyperextension) in a patient with severe rheumatoid arthritis, who had previously undergone decompression and an Occiput-T2 instrumented fusion for cranio-cervical and sub-axial cervical spine instability. Imaging showed fracture-subluxation of T1/2 and T2/3 with the bilateral C7, T1 and T2 screws in the mediastinum causing tracheal and esophageal compression. Removal of the instrumentation, decompression (T2 corpectomy) and construct revision down to T10 was safely performed from a posterior approach. Severe osteoporosis, some pre-existing screw loosening and hyperextension of the neck were the predisposing factors of this near catastrophic event. By staying directly posterior to the rod and following the fibrous tract already created, the instrumentation was safely removed from the mediastinum.